Analysis of the potential of memelong leaves (Philodendron giganteum) as an antioxidant and antimicrobial - Silitonga, Martha; Sitompul, Mutiara Rolika Putri; Gulo, Agnes; Anggeria, Elis (Jurnal Prima Medika Sains, 2024)
Ornamental plants are plants whose main function is to decorate. Many ornamental plants have benefits, one of which is the Philodendron plant. It is important to know the benefits of antioxidants and antimicrobials that ornamental plants have and can be used to improve health. The research aimed to determine the potential of Memelong (Philodendron giganteum) as an antioxidant and antimicrobial. The research carried out was empirical research at the FKKGIK UNPRI Laboratory for 1 month. The samples used were all Memelong leaves. Memelong leaf extract is made by maceration. Next, carry out phytochemical tests including alkaloid testing, flavonoid content testing, saponin testing, testing for the presence of tannins, and testing for triterpenoids and steroids. The antioxidant activity test was carried out using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The antimicrobial activity test was carried out using the paper disc diffusion method. Data analysis using univariate presented in the form of tables and graphs descriptively. The results of this study have potential as antioxidants based on antioxidant tests using the DPPH method with sample concentrations of 400 ppm 14%, 600 ppm 16%, 800 ppm 19%, and 1000 ppm 27%, but the results are still smaller when compared to the vitamin C test results. However, in the antibacterial activity test on Memelong leaf extract, there was no inhibition zone in the 25% formulation, an average of 0.50%, an average of 0.75%, an average of 0, the K(+) was found to be an average of 18,85 diameter of inhibition zone. The research conclusion is that the leaves of Memelong are proven to contain antioxidants.